ANALISIS DAN PERANCANGAN APPLICANT TRACKING SYSTEM - Soni, Soni; N, Hapsoro Renaldy; Sujiwo, Yogi (Bina Nusantara University, 2007)
The aim of the research was to design a web-based applicant tracking system to support Human ResourcesManagement system. Research methods were library study and system design. It can be concluded that the applicanttracking system is able to help HRD staff to chose staff candidates, manage recruitment time, create an applicantdatabase, and it can be function as a web bursa kerja site (EE).Keywords: applicant tracking system, candidate selection, employee recruitment